Eduard Gans y la idea de Europa - Ginzo Fernández, Arsenio (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2012)
This article is supposed to be an approximation to Eduard Gans´ conception of Europe, an author considered to be the most prominent disciple of Hegel by a growing number of scholars. In those times, the idea of Europe was a highly topical subject, due to both to the influence of the Enlightenment and the French Revolution, but as well to the development of German idealism. Gans is closely related to these instances and formulates an idea of Europe that goes beyond the conception of his teacher Hegel. He takes into account the new instances that arise from 1830 on in Europe, while he is also receptive to the views coming from America.